Penerapan Metode Eksperimen Sains Terhadap Keterampilan Sains Peserta Didik di TK Perjuangan Jalanjang Kabupaten Bulukumba - Mawaddah, Nurul; M. Yusuf. T; Hamansah, Hamansah (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to determine the application of experimental science methods among students at TK Perjuangan Jalanjang, Bulukumba Regency. This study employs a quantitative approach with an experimental method (pre-experimental), specifically a one-group pre-test post-test design. The population in this study consists of 18 individuals from TK Perjuangan Jalanjang, Bulukumba Regency, which includes 11 females and 7 males. The instrument used in this study is an observation guide for science skills. The data analysis technique employs inferential statistics, which includes normality tests and non-parametric statistical tests. Based on the analysis results, it can be concluded that the application of the science experiment method has an impact on improving the science skills of children at TK Perjuangan Jalanjang, Bulukumba Regency. The average score for the pre-test is 7.7 and the average score for the post-test is 22.7. It can be seen from the results of the Wilcoxon sing rank test that there is a significant difference with a Sig (2-tailed) value of 0.000 < 0.05, thus Ha is accepted and Ho is rejected. The implications of the research indicate that the application of the science experiment method affects the science skills of children